Transient restrictive cardiomyopathy in cats: first reported case series - Poissonnier, Camille; Guigo, Pierre; Foulex, Pierre; Passavin, Peggy; Fouhety, Aurore; Douay, Tiphaine; Le Gall, Coline; Kartout, Kahina; Bomassi, Éric; Chetboul, Valérie (Frontiers in Veterinary Science, 2025)
BackgroundTransient myocardial thickening has been reported in cats. This clinical entity is characterized by reversible left ventricular (LV) hypertrophy often associated with left atrial (LA) dilation and congestive heart failure (CHF) that resolves over time. To the best of our knowledge, transient restrictive cardiomyopathy (TRCM) has not yet been reported in cats.ObjectivesTo describe the epidemiological, clinical, echocardiographic, and prognostic features of cats with TRCM.Animals17 cats with TRCM and 16 control cats with non-transient RCM (NT-RCM).MethodsRetrospective study. Clinical records of cats with an RCM phenotype (defined by normal LV dimensions with LA or biatrial enlargement) were searched in 6 veterinary databases. Cats with subsequent resolution of the RCM phenotype were included in the TRCM group and those with persistent RCM phenotype in the NT-RCM group.ResultsTRCM cats were significantly younger than NT-RCM cats (p = 0.003). An antecedent event was identified 24 h to 17 days before diagnosis in most TRCM cats (11/17), but in no NT-RCM cat. All TRCM cats and 12/16 NT-RCM cats had CHF, with a lower left atrium:aorta ratio in TRCM cats (p = 0.04). Diuretic treatment was discontinued (10/17) or decreased (7/17) in all TRCM cats, but in no NT-RCM cat. Median survival time of NT-RCM cats was 667 days whereas the Kaplan–Meier method estimated that 86% of the TRCM cats had not died from cardiac death 6,000 days after diagnosis (p = 0.003).Conclusion and clinical importanceTRCM occurs in cats with common antecedent events and with excellent long-term prognosis in most cases.